Steven Muhlberger, The fifth-century chroniclers: Prosper, Hydatius, and the Gallic Chronicler of 452, Leeds, Francis Cairns Publ., 1990, XI + 329 pp. ISBN 0-905205-76-6 (Minerva. Revista de Filología Clásica, 2019)
Reseña de Steven Muhlberger, The fifth-century chroniclers: Prosper, Hydatius, and the Gallic Chronicler of 452, Leeds, Francis Cairns Publ., 1990, XI + 329 pp. ISBN 0-905205-76-6